Active Management of the Third Stage of Labour: A Brief Review and Update - Sultana, Nahid; Begum, Ferdousi; Shermin, Shahana (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Blood loss due to postpartum haemorrhage (PPH) and its complications constitute one ofthe major causes of maternal mortality and morbidity. Active management of third stage oflabour (AMTSL) plays an immense role in preventing maternal death due PPH. But till dateobstetricians all over the world and the concerned international bodies could not reach to asingle agreement about its universal use. This approach is practiced widely in many centresand there are some specific guidelines regarding its practical use. AMTSL as a prophylacticintervention and is composed of a package of three components or steps: 1) administrationof a uterotonic, preferably oxytocin, immediately after birth of the baby; 2) controlled cordtraction (CCT) to deliver the placenta; and 3) massage of the uterine fundus after the placentais delivered. In 2012, the results of a large WHO-directed, multi-centred clinical trial showedthat the most important AMTSL component was the administration of an uterotonic, theother two steps contributes relatively less in blood loss. But WHO recommends to continueall three steps of AMTSL for management and training of third stage of labour. This article isa brief review of the recent guidelines and evidence based practice of active management ofthe third stage of labour. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 149-156